Bolesław Sadaj (1908-1997) – badacz dziejów oświaty regionalnej - Żakowska , Barbara (Studia Edukacyjne, 2022)
The article is dedicated to Bolesław Sadaj’s research, with particular emphasis on his scientific achieve- ments in the field of historical and educational research. The article is based on source research, with the usage of a comparative and retrospective method. Based on the source query and analysis, it can be stated that Bolesław Sadaj’s research starting from 1946, i.e. the onset of Polish education in Szczecin, till the end of his professional activity in the 1990s, was significant and multidirectional. His out- put in the field of pedeutology and his works concerning the development of educational institutions in Szczecin Pomerania in the second half of the 20th c. constitute a major contribution to the history of pedagogical theory and practice, which places Bolesław Sadaj among historians of education and researchers of regional history.